Pengaruh Return On Asset, Current Ratio, Debt to Equity Ratio dan Inventory Turnover Terhadap Return Saham pada Perusahaan Sektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019 - Wahyu Alfrian Marindra; Easter Inisensia Simbolon; Laila Anjelia; Siti Dini (Universitas Batanghari Jambi, 2021)
Consumer Goods Sector Manufacturing Companies Listed on Bursa Efek Indonesia From 2017 until 2019 are the objects in this research. The purpose of this research is none other than to knowing how much ROA, CR, DER, and ITO affects the Stock Return. Data taken is the secondary data with sampling method using purposive sampling. Samples obtained for three years of research as many as 66. Analysis technique used is multiple linear regression, with the result obtained that Return On Asset has a positive and significant effect on Stock Returns, Current Ratio doesn’t have an effect and insignificant on Stock Returns, Debt to Equity Ratio doesn’t have an effect and insignificant on Stock Returns, and Inventory Turnover doesn’t have an effect and insignificant on Stock Returns at Manufacturing Companies in The Consumer Goods Industry Sector Listed on IDXin 2017 until 2019.